Bruner's Theory Constructivist Learning on the Ability to Understand Mathematical Concepts of Elementary School Students - Yunita Wildaniati; Ummi Nur Rokhmah; Susana Eka Dewi; Fattah Hanurawan; Ade Eka Anggraini (UIN Siber Syekh Nurjati Cirebon, 2024)
AbstractHaving the ability to understand concepts is fundamental to learning math, and it is important for students. This study is directed to examine the impact of Bruner's constructivist learning approach on elementary school students' ability to understand mathematical concepts. The type of research used is pre-experimental with a one group pre-test-post-test design. This study focuses on grade IV students from SDN 04 Ardirejo, Kepanjen Regency Malang. Data was collected using a written test in the form of a description of 5 points of pre-test questions and 5 points of post-test questions. Research data was analyzed using descriptive and inferential statistics with a paired sample t-test. The test results of the t test obtained that tcount is 20.065 while ttable is 2.059. Because 20,065 > 2,059, the tcount > ttable, it can be concluded that there is a significant influence from the application of Bruner's theoretical constructivism learning on the ability to understand mathematical concepts of grade IV students of SDN 04 Ardirejo, Kepanjen Regency Malang.Keywords: bruner's theory of constructivism, understanding mathematical concepts.AbstrakMemiliki kemampuan untuk memahami konsep adalah hal fundamental dalam belajar matematika, dan hal ini penting bagi siswa. Studi ini diarahkan untuk mengkaji dampak dari pendekatan pembelajaran konstruktivisme yang dikembangkan oleh Bruner, terhadap kemampuan siswa sekolah dasar dalam memahami konsep-konsep matematika. Jenis penelitian yang digunakan adalah pre eksperimental dengan desain one group pre-test-postest. Subjek dalam penelitian ini adalah siswa kelas IV SDN 04 Ardirejo Kepanjen Regency Malang. Pengumpulan data dilakukan dengan menggunakan tes tertulis bentuk uraian sebanyak 5 butir soal pretes dan 5 butir soal post-test. Analisi data penelitian dilakukan dengan menggunakan statistik deskriptif dan inferensial dengan uji paired sample t-test. Hasil pengujian uji t diperoleh bahwa thitung bernilai 20,065 sedangkan ttabel sebesar 2,059. Karena 20,065 > 2,059 maka thitung > ttabel sehingga dapat disimpulkan bahwa terdapat pengaruh yang signifikan dari penerapan pembelajaran konstruktivisme teori Bruner terhadap kemampuan pemahman konsep matematis siswa kelas IV SDN 04 Ardirejo Kepanjen Regency Malang.Kata kunci: konstruktivisme teori bruner, pemahaman konsep matematis.